Determination of Caco 3 and Sio 2 Content in the Binders of Historic Lime Mortars - Uğurlu Sağın, Elif; Böke, Hasan; Yalçın, Şerife; Aras, Nadir; Yalçın, Şerife; Aras, Nadir; Böke, Hasan; Uğurlu Sağın, Elif (Springer Verlag, 2012)
The binders of historic mortars composed of small grain sized silica (SiO 2) and carbonated lime (CaCO 3) are considered as the main part that give hydraulic character and high strength to the mortar. In this study, FTIR, SEM-EDS, LIBS and XRD spectroscopy were used to find out the weight ratios of CaCO 3 to SiO 2 in the binders of historic lime mortars. For this purpose, a series of pure calcium carbonate and silica mixture were prepared in ten combinations in varying ratios from 0.5 to 5. Calibration curve was prepared for each analysis by plotting the peak area or intensity ratios of CaCO 3 to SiO 2 versus the weight ratios of CaCO 3 to SiO 2. A good linear correlation coefficient was obtained for each analysis respectively. The analyses were then tested on the binder of the Roman mortar samples. The results indicated that FTIR, SEM-EDS and LIBS spectroscopy are convenient tools to determine the weight ratios of CaCO 3 to SiO 2 in the binders of mortars. But XRD spectroscopy is not convenient for quantitative analysis of binders due to the presence of varied amounts of amorphous or poor crystalline silica in their compositions.
Keywords: Binder; Calcite; FTIR; Historic mortar; LIBS; SEM-EDS